TRAIT ASSOCIATION ANALYSIS AND DIVERSITY ASSESSMENT IN BROWN TOP MILLET (Brachiaria ramose L.) GERMPLASM LINES - ANAND KUMAR; SK. SAMEENA; K. SRAVAN SIMHA REDDY; S. ANANDA RAJA KUMAR; P. CHANDRA OBUL REDDY; C. V. C. M. REDDY; A. CHANDRA SEKHAR (The Journal of Research ANGRAU, 2024)
The experiment was conducted during the year Rabi 2022. Eight purelines developed by the SSD method have been assessed along with six lines collected from RARS, Nandyal for various phenotypic traits such as number of tillers, plant height, days to 50% flowering, flag leaf length, number of leaves per plant, primary rachis length, panicle exertion length, types of panicle, length of panicle, days to maturity, panicle weight, and 1000 grain weight were recorded. Significant variation has been observed for most of the traits such as maturity days (76-83 days), days to 50% flowering (52.6-67 days), plant height (15- 30 inch), leaves number (19-24), primary rachis length (2.7-7.1 inch), flag leaf length (4.6-7.3 inch), panicle exertion length (1.43-2.33 inch), panicle length (4.7-9.1 inch), panicle weight (0.7-2.6 gm), panicle types (open and close), number of tillers (2-4) and 1000 grain weight (0.67-2.05 gm). Path coefficient, genotypic coefficient variation, and phenotypic coefficient variation facilitate understanding the trait association influenced by genetic and environmental factors. There was a strong positive correlation between the panicle effect and the weight of 1000 grains. High heritability was observed for the trait panicle type (100%), followed by 1000 grain weight (88%), primary rachis length (80.83%), panicle weight (70.6%), panicle exertion length (63.52) and panicle length (53.48). PC score illustrated, BTM-6 with the highest PC score (3.43) followed by BTM-7 (1.95), BTM-2 (0.89, and BTM-5 (0.83). The present study signifies the genotypic and phenotypic variability in browntop millet with respect to the quantitative and qualitative traits with breeding importance.